2007
DOI: 10.1111/j.1600-079x.2007.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and type 2 diabetes – a possible link?*

Abstract: The aim of the present study was to determine the existence of melatonin membrane receptors and to examine the mRNA expression of nuclear orphan receptors in human pancreatic tissue, in an effort to explain differences between type 2 diabetic and metabolically healthy patients. Molecular and immunocytochemical investigations established the presence of the melatonin membrane receptors MT1 and MT2 in human pancreatic tissue and, notably, also in the islets of Langerhans. Results of a calculation model to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
164
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(180 citation statements)
references
References 45 publications
(77 reference statements)
9
164
1
6
Order By: Relevance
“…In view of the effects of melatonin on islets and on whole body metabolism, a link between melatonin receptors and type 2 diabetes was suggested [63] following the demonstration of increased levels of MTNR1A and MTNR1B mRNA in pancreatic tissue from patients with type 2 diabetes and increased immunolabelling of MTNR1A and MTNR1B. Although these results were qualitative rather than quantitative, it was postulated that there is a link between the melatonin system and the pathogenesis of the disease.…”
Section: Genome-wide Association Studies and Mtnr1bmentioning
confidence: 99%
“…In view of the effects of melatonin on islets and on whole body metabolism, a link between melatonin receptors and type 2 diabetes was suggested [63] following the demonstration of increased levels of MTNR1A and MTNR1B mRNA in pancreatic tissue from patients with type 2 diabetes and increased immunolabelling of MTNR1A and MTNR1B. Although these results were qualitative rather than quantitative, it was postulated that there is a link between the melatonin system and the pathogenesis of the disease.…”
Section: Genome-wide Association Studies and Mtnr1bmentioning
confidence: 99%
“…Two distinct G proteincoupled receptors, MTNR1A and MTNR1B, mediate the effects of melatonin. These two receptors have been found to be produced in human pancreatic islets [9,10], and the levels of both are upregulated in type 2 diabetic patients [11]. Furthermore, Lyssenko et al [3] confirmed the presence of MTNR1B in human pancreatic islets and showed increased MTNR1B mRNA expression in carriers of the rs10830963 risk genotype, reporting a negative correlation between MTNR1B mRNA levels and insulin secretion.…”
Section: Introductionmentioning
confidence: 97%
“…Human and rodent pancreatic tissues and islets and rodent cell lines has been found to express MT1 and MT2 receptors (10,35,53,55,(61)(62)(63)(64)(65). The occurrence of melatonin receptors in the pancreatic islets proposes that their activation by melatonin might directly influence insulin or glucagon production and provides a biochemical basis to explain how decreased melatonin levels of diabetic patients could affect the function of the pancreas (6,66).…”
Section: Melatonin and Insulin Secretionmentioning
confidence: 99%
“…A low quantity of circulating melatonin occur in patients with type 2 diabetes (11), at the same time upregulated mRNA expression of melatonin membrane receptor was observed (55). Furthermore, polymorphisms in the melatonin receptor gene were linked with fasting blood glucose level and susceptibility to the occurrence of type 2 diabetes (56).…”
Section: Melatonin and Glucose Homeostasismentioning
confidence: 99%
See 1 more Smart Citation